The Degree of Availability of Human Resource Risk Management Components in Yemeni Universities According to International Risk Management Standards (ISO31000:2018): A comparative study - Yahya Shaker, Abdalmilk Mohammed; Ali Omar, Khadija; Ali Yahya, Atef (Social Empowerment Journal, 2025)
The aim of the research was to identify the degree of availability of human resources risk management components in Yemeni public and private universities according to international risk management standards (ISO31000:2018). The comparative approach was used, and the questionnaire tool consisted of (37) paragraphs, distributed over three axes representing the components of risk management (principles, system, operations). The questionnaire was applied to the research sample members, numbering (198) individuals, from the academic and administrative leadership in Yemeni public and private universities, including (university presidents and their deputies, deans of quality, secretaries-general). The most prominent results of the research were: The degree of availability of human resource risk management components (principles, system, processes) in public universities according to the international standards for risk management (ISO31000:2018) was rated as “low”, with an arithmetic mean of (2.57) and a percentage of (52%), while the degree of availability of human resource risk management components (principles, system, processes) in private universities according to the international standards for risk management (ISO31000:2018) was rated as “average”, with an arithmetic mean of (3.04) and a percentage of (61%). The results did not show any statistically significant differences at a significance level of (0.05) between the average responses of sample members regarding the degree of availability of human resource risk management components (principles, system, processes) according to the variable of university type.